The Silence of Men, reflected in “Heroides”, the imaginary letters of love written by Publius Ovidius Naso (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
In this paper, we aim to analyse the set of imaginary letters entitled Heroides, written by Publius Ovidius Naso. Employing the elegiac distich, the Latin poet transcends the familiar narrative threads of Greek and Roman myths and legends to explore the intimate impulses that animate the love relationships between famous characters, such as Penelope and Odysseus, Briseis and Achilles, Dido and Aeneas, among others. In recent years, these letters have been re-examined through the lens of gender studies, shifting the critical focus from the frustrated and grieving women to the male perspective on the love relationships. In this article, however, we do not aim to analyse the actions or words of the male characters, but their silences, which are laden with multiple meanings. The theoretical framework will draw upon Max Picard’s The World of Silence (1948) and Adam Jaworski’s The Power of Silence. Social and Pragmatic Perspectives (1993). Our discussion will focus on the relevance of silence for the actants: how they employ it, the reasons they approve or disapprove of it, and the connections between silence and spoken or internalized words.
Keywords: silence; frustration; emancipation